2017
DOI: 10.18632/oncotarget.15339
|View full text |Cite
|
Sign up to set email alerts
|

The combined action of mast cell chymase, tryptase and carboxypeptidase A3 protects against melanoma colonization of the lung

Abstract: Mast cell secretory granules are densely packed with various bioactive mediators including proteases of chymase, tryptase and CPA3 type. Previous studies have indicated that mast cells can affect the outcome of melanoma but the contribution of the mast cell granule proteases to such effects has not been clear. Here we addressed this issue by assessing mice lacking either the chymase Mcpt4, the tryptase Mcpt6 or carboxypeptidase A3 (Cpa3), as well as mice simultaneously lacking all three proteases, in a model o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 47 publications
1
28
1
Order By: Relevance
“…However, it is notable that our findings are in line with a previous study where we showed that the collective absence of all of the proteases expressed by connective tissue‐type MCs led to a higher colonization of lungs with melanoma cells following their i.v. administration (Grujic et al, ). Moreover, our findings are consistent with clinical evidence in support of a correlation between MC protease expression and protection against melanoma (Crincoli et al, ; Siiskonen et al, ; Stieglitz et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is notable that our findings are in line with a previous study where we showed that the collective absence of all of the proteases expressed by connective tissue‐type MCs led to a higher colonization of lungs with melanoma cells following their i.v. administration (Grujic et al, ). Moreover, our findings are consistent with clinical evidence in support of a correlation between MC protease expression and protection against melanoma (Crincoli et al, ; Siiskonen et al, ; Stieglitz et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In that study, we found that MCs had an overall detrimental impact (Öhrvik et al, ) and to dissect the underlying mechanism we assessed mice lacking all of the MC proteases in the same model. Strikingly, we found that mice with global MC protease deficiency, contrary to the mice lacking MCs altogether, developed larger tumors than did WT mice (Grujic et al, ). This suggests that the combined action of the MC proteases serves a protective function in this model of melanoma, that is, despite the overall negative impact of MCs.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Mast cells are a major source of histamine, and histamine was shown to inhibit tumor growth by promoting the development of monocyte-derived DCs [93]. The combined deficiency in mast cell chymase, tryptase, and carboxypeptidase A3 was associated with reduced invariant NKT cells and increased melanoma dissemination [94]. Contrary to these reports on suppressive roles of mast cells in tumor progression, there are reports on enhancing roles of mast cells.…”
Section: Involvement Of Kir2dl4 On Human Mast Cells In Tumor Progressionmentioning
confidence: 99%
“…Mast cells produce Th2 cytokines which contributes to M2 (pro-tumor) polarization of tumor-associated macrophages, and the cells produce TNF-α and IL-10 which promote the Treg-mediated immune tolerance and immune tolerance against tumors [4][5][6]. Mast cells produce TGF-β, CXCL8, and TNF-α, promoting epithelial-to-mesenchymal transition in tumor invasion and metastasis [94][95][96]. Mast-cell-produced histamine was shown to inhibit hypoxia inducible factor-1 alpha expression and the followed growth suppression in melanoma [97].…”
Section: Involvement Of Kir2dl4 On Human Mast Cells In Tumor Progressionmentioning
confidence: 99%